COVID-related choroiditis masquerading as a choroidal melanoma - A.F. Brovkina; S.Yu. Nechesnyuk; A.V. Dobroserdov (РМЖ "Клиническая офтальмология")
A.F. Brovkina1,2, S.Yu. Nechesnyuk2, A.V. Dobroserdov2 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2S.P. Botkin City Clinical Hospital, Moscow, Russian Federation In the last two years, considerable attention has focused on eye disorders in the COVID-19 infection. The damage to the inner tunic of the eye is the most dramatic. The authors address hemodynamic abnormalities in these patients occurring during the disease and in the post-COVID-19 syndrome as demonstrated by optical coherence tomography (OCT) and OCT angiography (OCTA). Clinical presentations of COVID-related choroiditis are similar to those of other choroidites. This paper discusses a 66-year-old man with COVID-related choroiditis masquerading as choroidal melanoma who experienced the COVID-infection in April–May 2021. Clinical echographic signs of COVID-related choroiditis are described. The pathomorphology of this condition is uncovered for the first time. By comparing morphological signs in the choroid typical for cell damage with viruses and signatures of the pathological process in the inner tunic of the eye, the disease was interpreted as a COVID-associated  choroiditis. The authors conclude that attention should be paid to both early vision loss and its rate when differentiating between tumor- and non-tumor-related choroid disorders. Keywords: choroiditis, COVID-19, vasculitis, choroid disorders, choroidal melanoma, uveal melanoma. For citation: Brovkina A.F., Nechesnyuk S.Yu., Dobroserdov A.V. COVID-related choroiditis masquerading as a choroidal melanoma. Russian Journal of Clinical Ophthalmology. 2022;22(3):197–202 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-197-202.